CNT-based bifacial perovskite solar cells toward highly efficient 4-terminal tandem photovoltaics. Issue 4 (22nd February 2022) - Zhang, Chunyang; Chen, Min; Fu, Fan; Zhu, Hongwei; Feurer, Thomas; Tian, Wenming; Zhu, Chao; Zhou, Ke; Jin, Shengye; Zakeeruddin, Shaik Mohammed; Tiwari, Ayodhya N.; Padture, Nitin P.; et al.
Abstract : We describe highly efficient and stable bifacial perovskite solar cells incorporating carbon nanotube network films as a back contact enabling perovskite/CIS 4-terminal tandem solar cells to reach apower conversion efficiency of over 27%. Abstract : Carbon-based perovskite solar cells (C-PSCs) are recognized as low-cost stable photovoltaics. However, currently most highly efficient C-PSCs are optically opaque, which means that they can only utilize direct illumination but cannot efficiently utilize the reflected irradiance. Here we propose bifacial C-PSCs incorporating transparent carbon-nanotube (CNT) network films in the rear electrode to efficiently utilize the reflected irradiation. By systematically optimizing the type and size of representative CNTs (including MWCNTs and SWCNTs), we find that the SWCNT-PSCs show a monofacial-power-conversion-efficiency (monofacial-PCE) of up to 21.4%, whereas the SWCNT-PSCs reach a bifacial power output of 24.0 mW cm −2 in natural reflecting surroundings (20% of AM 1.5 G irradiance) and 34.1 mW cm −2 in artificial reflecting surroundings (100% of AM 1.5 G irradiance). The bifacial SWCNT-PSCs also show high operational stability with a loss of 5% under 1000 h full sun continuous illumination. Moreover, we achieved a PCE of 27.1% by using our bifacial device as a top cell together with a CIS bottom cell in a 4-T tandem. These findings point to a promising direction for improving the output power per unit area of PSCs.